1989
DOI: 10.1080/02652038909373742
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme immunoassay for the anabolic agent zeranol

Abstract: A competitive enzyme immunoassay (EIA) for the detection and quantitation of zeranol has been developed. The assay involves the use of excess second antibody adsorbed onto the walls of a microtitration plate well. Enzyme-labelled zeranol, prepared by the N-succinimidyl ester method, and standard or samples are added to the wells followed by zeranol-specific monoclonal antibody. The working range of the EIA is between 10 and 800 pg/well with a limit of detection of 10 pg/well (CV less than or equal to 10%). Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Fractions of 0.75 min were collected, the ZEA-oxime was detected photometrically at 274 nm. Fractions containing the derivative (30)(31)(32)(33)(34)(35)(36)(37) were pooled, and the solvent evaporated. An activated ester (18) waq formed with ZEA-oxime (5.25mg) by reaction with NHS (10mg) and DCC (35mg) in DMF (0.3ml) for 16 h at room temperature.…”
Section: Preparatton Of the Zearalenone Immunoreagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractions of 0.75 min were collected, the ZEA-oxime was detected photometrically at 274 nm. Fractions containing the derivative (30)(31)(32)(33)(34)(35)(36)(37) were pooled, and the solvent evaporated. An activated ester (18) waq formed with ZEA-oxime (5.25mg) by reaction with NHS (10mg) and DCC (35mg) in DMF (0.3ml) for 16 h at room temperature.…”
Section: Preparatton Of the Zearalenone Immunoreagentsmentioning
confidence: 99%
“…In order t o provide rapid and simple methods t o assay mycotoxins in foods and feeds that do n o t require extensive laboratory equipment, immunoassays have been shown t o be good alternatives t o conventional physico-chemical methods (23). Enzyme immunoassays (EIA) have been described for D O N -t y p e (4, 17, 26, 40,43) and ZEA-type (9, 21, 30,41) mycotoxins. I n this report w e describe the development of a highly sensitive EIA specific for ZEA-type mycotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of reactivity against a-zearalenol is of particular importance because antibodies used in past methods have always shown significant cross-reactivity against this compound, typically ranging from 21 to 54%. 6,7,15,19,20 With the exception of taleranol, the reactivity profile was slightly better than that obtained in an ELISA system also employing the specificity-enhanced zeranol antibody. 14 The cross-reactivity against taleranol was three times higher in the current study but still in the range found in some other zeranol antibodies.…”
Section: Resultsmentioning
confidence: 85%
“…3 A number of immunochemical methods have been developed for the screening of zeranol. [4][5][6][7] However, all the current immunochemical tests exhibit cross-reactivity to a greater or lesser extent with zearalenone, a-zearalenol and b-zearalenol, the three principal toxins produced by Fusarium spp. fungi.…”
Section: Introductionmentioning
confidence: 99%